2015
DOI: 10.1021/acs.jpcb.5b08431
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Electronic Structure of Cobalt(II) Ion in Nonplanar Porphyrins and Tracking of a Cross-Hybrid Stage: Implications for the Distortion of Natural Tetrapyrrole Macrocycles

Abstract: The core size of the porphyrin macrocycles was closely related to their stability of the different electron structure in the central metal ion. Cobalt(II) ions can undergo a conversion in electron configurations upon N4 core contraction of 0.05 Å in nonplanar porphyrins, and these ions still maintain low spin forms after and before conversion. The structural fine-tuning can induce the appearance of a cross-hybrid stage [d(x(2)-y(2))sp(2) ↔ d(z(2))sp(2)] based on quadrilateral coordination of the planar core. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 71 publications
6
28
1
Order By: Relevance
“…For zinc complexes 7 ‐Zn to 3 ‐Zn, the spectral shifts show a continuous trend because of the invariability of the zinc(II) ion . For complexes 7 ‐M to 3 ‐M [M = Fe III Cl, Co II ],, the continuity of the spectral shift trend is interrupted, as previously reported. The differential spectroscopic method can be used to track changes in the electronic structures of metal ions in nonplanar porphyrins.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…For zinc complexes 7 ‐Zn to 3 ‐Zn, the spectral shifts show a continuous trend because of the invariability of the zinc(II) ion . For complexes 7 ‐M to 3 ‐M [M = Fe III Cl, Co II ],, the continuity of the spectral shift trend is interrupted, as previously reported. The differential spectroscopic method can be used to track changes in the electronic structures of metal ions in nonplanar porphyrins.…”
Section: Resultssupporting
confidence: 77%
“…An inspection of the plot shows that the structures of the three metal ions in the model porphyrins can be changed and their diameters are mutually independent of each other. It has been shown that changing the macrocycle core size can directly change the electronic structures of iron(III), and cobalt(II) , . A similar effect is seen for nickel(II); the conversion point is between n C = 4 and 5 (Figure , labeled ☆), which is in agreement with the position derived from the spectral deviation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanoparticles have been proved to be unique hollow structures by transmission electron microscope (TEM) images (Figure d). The high‐resolution TEM and selected‐area electron‐diffraction (SAED) images (Figure e) reveal typical polycrystalline features of the hollow particles, which is derived from the irregular vacancy diffusion, identifying the particle as Co 3 O 4 nanoparticle (JCPDS No. 42‐1467).…”
Section: Figurementioning
confidence: 99%
“…Studies of model systems provide predictions of how ruffling will impact cobalt porphyrin electronic structure. In one study, Wang and Zhou found that enhancing Co(II) porphyrin ruffling increases the amount of spin density in the Co(II) d(z 2 ) orbital, which has implications for the interaction with substrate and reaction pathways. In another example, Grinstaff showed that highly distorted halogenated iron porphyrins catalyze alkane oxidation .…”
Section: Discussionmentioning
confidence: 99%